''Patients and clinicians perspectives on conventional and proprioceptive derivation approach'': focus on learning and experiencing new skills. (4th May 2023) - P, Mohan Kumar; Praveen, D; Ramana Murthy V, Venkata; P, Chaitanya; Sajjan, Girija S.; K, Mohana
Abstract: Background & Objective: Recent studies have shown that over 60% of dentists have any musculoskeletal disorders during their professional life. This study aimed to evaluate the effect of comfort levels of patients and clinicians while performing standard oral prophylaxis by ultrasonic scaling. Methods: A questionnaire was distributed among the patients and clinicians to record their perceptions on comfort levels, treatment satisfaction and efficiency levels on both conventional and Pd. Fifty Patients were included in group A, those in which non-surgical periodontal therapy was done in any two quadrants on a conventional dental chair. Group B consisted of 50 Patients, those in which non-surgical periodontal treatment was done in other two quadrants on Pd support. Results: Positive and negative aspects towards both the approaches by clinicians and patients regarding comfort levels, efficiency, and satisfactory levels were assessed and were more related to the Pd method. Clinicians are more comfortable when they used Pd approach, and everyone liked it. Conclusions: By following the Pd concept in dentistry, one can increase the longevity of dentists to work in their profession mainly by altering the workspace/environment and changing into Pd support instead of a dental chair.